Estimativa do estado nutricional de arroz irrigado por alagamento - Pocojeski, Elisandra (2007)
The difficulty to predict the intensity of soil properties alterative by soil flooding frequently makes the interpretation of the soil analysis results inaccurate when considering nutrients availability to the plants. Complementary methods of soil analysis, as leaf tissue analysis, chlorophyll meter and the leaf color chart can be used in order to estimate plants nutritional state. The objective of this study were: 1) to verify the influence of the cultivar, development stages and part of the plant on macronutrient levels and their relation with the rice productivity and 2) to monitory nitrogen (N) during the rice cycle in different conditions of N availability and to different cultivars of flooded rice, measuring chlorophyll meter and leaf color chart. In order to accomplish this task two field experiments were developed, during the agricultural year of 2005/2006, at Federal University of Santa Maria (RS). The first experiment studied, six cultivars of flooded rice with different cycles length (BR-IRGA 409, BR-IRGA 410, IRGA 417, IRGA 421, EPAGRI 108 e HÍBRIDO 2). Parts of the plants were collected in different periods and the macronutrients were analyzed, as well, the dry matter production, nutrients storage in the plant tissue and grain productivity were determined. The second experiment was installed comparing different N rate (0, 50, 80, 120 e 160 kg N ha-1) and two ways of nitrogen (N) application in dressing (before and after flooding). The first experiment with the six cultivars of flooded rice was also used. Measurements with chlorophyll meter arid, leaf color chart and N content analyses were done in the tissue during the crop cycle. Also, the dry matter production, stored N and grain productivity in both experiments was determined. There was a macronutrient level difference among the cultivars in the plant tissue, according to the collected part of the plant and the evaluation period. The plant part collected had greater influence on N and Ca levels and little influence in the levels of P, K and Mg. The levels of macronutrients of the plant parts and the assessment period are not significantly correlated with the grain productivity. The chlorophyll meter and the leaf color chart were sensible in diagnosing the availability of N for analyzed leaf, for different conditions of N availability. The cultivars show difference of N status, when assessed by the chlorophyll meter and the leaf color chart. With lower sensibility, the leaf color chart might be an alternative method to the chlorophyll meter if the cultivar factor is taken in consideration.